Investigation of the PhoPR two-component signal transduction system in Bacillus subtilis, Staphylococcus aureus and Staphylococcus epidermidis - Prunty, Michael (Trinity College (Dublin, Ireland). Department of Genetics, 2017)
The objectives of this study were (i) to establish the mechanism by which the PhoPR TCS is activated and deactivated in Bacillus subtilis subsp subtilis (strain 168) and subsp spizizenii (strain W23) and (ii) to determine the physiological roles of the PhoPR TCS in Staphylococcus aureus and Staphylococcus epidermidis. There were several reasons to study the PhoPR TCS in this cohort of bacteria. In B. subtilis subsp subtilis, Botella et al., (2014) showed that PhoR autokinase activity was inhibited by the WTA biosynthetic intermediate lipid III composed of poly(glycerol phosphate), a crucial feature of the mechanism by which the PHO response is amplified. This observation prompted two questions: (1) how is PhoPR initially activated upon phosphate limitation in B. subtilis subsp subtilis and (2) how is PhoPR initially activated and PhoPR activity controlled in B. Subtilis subsp spizizenii where WTA is composed of poly(ribitol phosphate). The PhoPR TCS in staphylococci was investigated to establish its physiological function with a particular focus on potential involvement in the regulation of WTA metabolism. Both S. aureus and S. epidermidis were chosen for study because they differ in the polyol composition of their WTA (i.e. poly(ribitol phosphate) and poly(glycerol phosphate) respectively), a feature that is important for regulation of PhoPR activity in bacilli species.
Keywords: Genetics & Microbiology, Ph.D.; PhD Trinity College Dublin, 2017